2013
DOI: 10.1016/j.jaapos.2013.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative visual acuity and contrast sensitivity in children with small, partial, or non-central cataracts

Abstract: Background While there is clear evidence that dense central cataracts >3 mm diameter warrant prompt intervention to prevent deprivation amblyopia, guidelines for management of small, partial and non-central cataracts are not evidence-based. Consensus guidelines advise managing affected infants and preschool children by monitoring for possible progression in size or density and pharmacologic pupillary dilation, if indicated. Extraction is deemed necessary if the cataract progresses sufficiently to obscure the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Several reports suggest it is clinically reasonable to measure CS to assess visual system disability in patients with multisystem vision disease [21,[34][35][36][37]. Anatomical and electrophysiological anomalies found in human albinos are reflected by reduced contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports suggest it is clinically reasonable to measure CS to assess visual system disability in patients with multisystem vision disease [21,[34][35][36][37]. Anatomical and electrophysiological anomalies found in human albinos are reflected by reduced contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical and electrophysiological anomalies found in human albinos are reflected by reduced contrast sensitivity. Testing of CS in patients with INS has repeatedly shown it to be abnormal [21,[34][35][36][37]. High astigmatic errors, nystagmus and other retinal/neural anomalies may result in abnormal meridional differences in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In a recent report, Birch et al found that abnormal visual acuity and contrast sensitivity in young children with partial cataracts was associated with poor long-term visual acuity outcomes. 63 This suggests that while conservative treatment can be used, it must be done so with caution, and ancillary tests such as glare testing must be utilized to ensure the lens opacity is not visually significant.…”
Section: Managementmentioning
confidence: 99%
“…[2][3][4] Thus contrast sensitivity testing is recommended in the assessment of visual impairment and for use in low vision clinics. 5 Furthermore, studies have shown that contrast sensitivity assessment can aid in the detection and evaluation of the progression of ocular diseases such as optic neuritis, 6,7 infantile and age-related cataract, [8][9][10][11] glaucoma, 9,10 age-related macular degeneration, 11 stroke patients, 12 thyroid-associated ophthalmopathy 13 and amblyopia. 14 A study by the Cryotherapy for Retinopathy of Prematurity Cooperative Group demonstrated the effect of cryotherapy on visual functions.…”
Section: Introductionmentioning
confidence: 99%